An Investigation on Engineering Properties of Composite Beam - Sayed Javid , Azimi; Sharifah Maszura, Syed Mohsin; Fadzil, Mat Yahaya; Abdoullah, Namdar (Maxwell Scientific Organization, 2014)
There is several agriculture waste materials have continuously been producing. The oil palm shell has been used to produce Oil Palm Shell Concrete (OPSC). And by use of 1% Kenaf-Oil Palm Shell mixture, a natural composite concrete (OPS-kenaf concrete) has been made. The time to failure, stroke and flexural strength of concrete beams have been studied. The concrete cubes have also been tested to identify time to failure and compressive strength of proposed concretes. The results have been indicated that 1% kenaf-OPS mixture enhances flexural strength of beam. And also the stroke and time to failure have not considerably been changed. The significant effect has not been observed on morphology of crack. The compressive strength of (OPS-1% kenaf mixture) has been improved. This new proposed composite concrete beam has acceptable effect on minimizing environment pollution.